1997
DOI: 10.1029/96jb03115
|View full text |Cite
|
Sign up to set email alerts
|

Double beam imaging: Mapping lower mantle heterogeneities using combinations of source and receiver arrays

Abstract: Abstract. We present a new technique for imaging spatially distributed heterogeneities using information from combinations of source and receiver arrays. The method is based on the single scattering assumption and is closely related to the double beam method of Kriiger et al. [ 1993, 1995, 1996] in that it exploits amplitude, delay time, slowness, and azimuth information in two arrays simultaneously. A crucial step in the method is the application of static time corrections for a chosen reference phase (here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 35 publications
2
70
0
Order By: Relevance
“…For while it is tempting to interpret the D″ discontinuity in terms of a mineralogical phase change on the basis of this being the cause of the 410 and 660 discontinuities, the D″ region is the boundary layer between the solid silicate mantle and the liquid outer core, where great thermo-chemical complexity is already expected in the absence of a phase transition. Thus, the D″ discontinuity may instead represent reflections (or scattering, Scherbaum et al 1997) off small-to regional-scale thermo-chemical heterogeneities, such as subducted slabs (Christensen 1989;Christensen and Hofmann 1994), piles or layers of dense and possibly primitive material (Davies and Gurnis 1986), and core-mantle reaction products (Knittle and Jeanloz 1989). The localised nature of these structures provides a plausible mechanism for the lateral variations in the depth, strength and visibility of the D″ discontinuity (Sidorin et al 1998).…”
Section: The D″ Discontinuitymentioning
confidence: 95%
See 1 more Smart Citation
“…For while it is tempting to interpret the D″ discontinuity in terms of a mineralogical phase change on the basis of this being the cause of the 410 and 660 discontinuities, the D″ region is the boundary layer between the solid silicate mantle and the liquid outer core, where great thermo-chemical complexity is already expected in the absence of a phase transition. Thus, the D″ discontinuity may instead represent reflections (or scattering, Scherbaum et al 1997) off small-to regional-scale thermo-chemical heterogeneities, such as subducted slabs (Christensen 1989;Christensen and Hofmann 1994), piles or layers of dense and possibly primitive material (Davies and Gurnis 1986), and core-mantle reaction products (Knittle and Jeanloz 1989). The localised nature of these structures provides a plausible mechanism for the lateral variations in the depth, strength and visibility of the D″ discontinuity (Sidorin et al 1998).…”
Section: The D″ Discontinuitymentioning
confidence: 95%
“…It is more problematic to invoke post-perovskite for explaining observations of the D″ discontinuity underneath Siberia/Eurasia, where large-amplitude, positive polarity PdP phases, indicative of large (1-3 %) increases in P wave speed, have been documented by multiple studies (e.g. Weber and Davis 1990;Houard and Nataf 1992;Weber 1993;Scherbaum et al 1997;Thomas and Weber 1997). Thomas et al (2011) suggested that these large P wave speed increases may still be reconciled with a phase change from Pv to pPv, if the pPv grains are aligned due to flow, and the seismic waves preferentially sample the fast crystallographic direction.…”
Section: Velocity and Density Contrastsmentioning
confidence: 96%
“…In this study we use a concept of likelihood of single scattering [Scherbaum et al, 1997]. For each grid point in a region around the foci we compute a "probability" or "likelihood" with which the point can scatter incoming waves from the source to the arrays to be observed as the 90s phase Another piece of evidence which supports the S-to-P scattering model comes from an analysis of one shallower event (with depth 475 to 495 km, 93092 in Table 1).…”
Section: Joint Likelihood Of Scatteringmentioning
confidence: 99%
“…The resolution can be enhanced by combining source and receiver arrays (double beam method DBM) [Kriiger et al, 1996]. The DBM was previously applied to cluster-s of nuclear explosions to image lower mantle heterogeneities [Scherbaum et al, 1997], and microearthquakes [Rietbrock and Scherbaum, 1999]. Source arrays of deep earthquakes can especially be useful in the identification of scattering objects in the mantle.…”
Section: Introductionmentioning
confidence: 99%